Nasal swabs are more effective than groin swabs in detecting MRSA in newborn infants. (29th September 2015) - Duffy, D; Garbash, M; Kennea, N
Abstract : Background: Neonatal units have experienced an increase in MRSA prevalence.1 MRSA may result in infectious morbidity and is a surrogate marker of cleanliness for health authorities. Policies for surveillance vary widely across adult, paediatric and neonatal intensive care facilities.2 Aim: Describe the frequency of MRSA positivity and whether nasal and/or groin swabs are needed to identify colonisation. Methods: Nasal and groin swabs were taken simultaneously on admission to the neonatal unit and twice weekly thereafter. Swab results from all admissions (including transfers from other units) over a 1-year period (2007) were analysed. Results: A total of 2396 MRSA swabs were cultured in 354 babies. Overall 65/2396 swabs (2.8%) were positive. 43/1202 (3.6%) nasal swabs were positive compared to 22/1194 (1.8%) groin swabs. (p=0.01). Sites of positive swabs when taken at the same time- nasal only: 25/47 (53%); nasal and groin: 21/47 (45%); groin only: 1/47 (2%). 11/354 (3.1%) babies were culture positive for MRSA. (birth weight: mean 1466 g, range 630 g–4270 g; gestational age: mean 30 weeks, range 24–41 weeks). Compared to MRSA negative babies, positive babies were more likely to be lower birth weight and gestation. Swabs were first found to be culture positive at a mean of 15.6 days (range 7–69 days). When first detected as MRSA positive, sites of positive swabs were- nasal only: 5/11 (45.5%); nasal and groin: 5/11 (45.5%); groin only: 1/11 (9%). (This infant was first culture positive from groin swab on day 7, no subsequent swabs collected; born at 41 weeks gestation, all other positive babies born at or below 32 weeks gestation). Conclusion: Nasal swabs show a much higher positive detection rate both overall and when babies are first colonised with MRSA. Analysing surveillance swabs from only the nasal site is an effective policy for MRSA detection.